The Efficacy of Gabapentin in the Treatment of Pain Due to Far Lateral Lumbar Disc Herniations - Ozturk, Sait; Ucler, Necati; Hergunsel, Omer Batu; Gulkesen, Arif; Kaplan, Metin (Lippincott Williams & Wilkins, 2016)
Objectives: Far lateral lumbar disc herniations (FLLDHs) can cause difficulty and differences in diagnosis and treatment compared with intraspinal herniation. We have aimed to analyze the efficacy of gabapentin as a noninvasive treatment of pain in patients with isolated FLLDH. Methods: Thirteen patients with isolated FLLDH were evaluated for the study prospectively. All of the cases were diagnosed by lumbar magnetic resonance imaging. The previously prescribed medical therapy of the patients was not changed and gabapentin (3 x 600 mg/d) was added. For each patient, visual analog scale and Odom criteria were administered and recorded at 4 time points as follows: pretreatment and days 1, 7, and 30 post-treatment. Paired t test was used to examine scores of the cases before and after gabapentin treatment. Results were considered significant at P < 0.05, and 95% confidence interval was calculated. Results: Mean visual analog scale score was 9.3 in the pretreatment period, and reduced to 5, 2.6, and 1.3 on posttreatment days 1, 7, and 30, respectively (P < 0.05). Mean Odom criteria score was 4 before gabapentin treatment. It decreased to 2.3 at posttreatment day 1 and 1.5 at day 7. At the end of 1 month, symptoms had resolved completely in all cases (P < 0.05). Conclusions: Gabapentin provided fast and effective relief of pain caused by FLLDH. We advise that the gabapentin should be kept in mind in the first-step medication of pain for such patients. Direct compression of the dorsal root ganglion or its distal part may be related to the intense pain-relief effect provided by gabapentin.
Keywords: gabapentin; far lateral; disc herniation; pain